Predictive importance of cartilage acetabular index for acetabular dysplasia in orthopedic surgery - Mehmet Onur Ziyadanoğulları; Hüseyin Arslan (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To investigate the relationship between the cartilage acetabular index and acetabular development and secondary dysplasia. Methods: A total of 58 hips underwent intraoperative arthrography-guided open reduction or limited open reduction due to developmental hip dysplasia between 2011 and 2015 was included in the study. We evaluated patients with acetabular angle 8º as group 2. Intraoperative acetabular cartilage index measurements were performed, and patients with low and high cartilage acetabular index were divided into two groups. Results: There was a correlation between the cartilage acetabular index value, which indicates preoperative cartilage acetabular coverage, and acetabular development and secondary acetabular development. Conclusion: The cartilage acetabular index is a technically easy and uncomplicated evaluation method that can be used to estimate acetabular development and should be used routinely together with the bone acetabular index.